First report of potato virus S naturally infecting arracacha (Arracacia xanthorrhiza) in Peru - Souza, J. de; Gamarra, H.; Muller, G.; Kreuze, Jan F. (Scientific Societies, 2018)
Potato virus S (PVS, genus Carlavirus, family Betaflexiviridae) naturally infects potato (Solanum tuberosum) and pepino (S. muricatum) and experimentally can infect other species of the families Solanaceae and Chenopodiaceae. Two strains of PVS have been described: PVSO (ordinary) and PVSA (Andean), depending on the symptoms induced on Chenopodium quinoa. In potato, PVS can cause yield losses of up to 20% (Stevenson et al. 2001). Arracacha (Arracacia xanthorrhiza) is an Andean root crop grown mainly in Peru, Colombia, Ecuador, Brazil, and Bolivia (Hermann 1997). Using newly designed universal primers confirmed to amplify fragments of the RdRp region of carlaviruses from potato and sweet potato, we could amplify a 340-bp band from an asymptomatic arracacha plant collected on August 2011 from a smallholder in Cajamarca, Peru. The fragment was sequenced, revealing closest nt similarity of 76% with a sequence of PVS (JQ647830.1) available in GenBank. We then tested 20 arracacha accessions from the CIP Germplasm bank with the same primers and detected one positive plant (CIP204060; isolate Pasco), originally from Oxapampa, Peru, whose PCR fragment had 83% nt identity to the previous fragment isolated and 79% nt identity with a PVS sequence from GenBank (CAA75715.1). Neither of the positive arracachas showed symptoms or reacted with PVS antibody (produced at CIP) in DAS-ELISA. Mechanical transmission of accession CIP204060 to indicator plants (Nicotiana debneyii, N. bigelobii, N. occidentalis, N. clevelandii, Gomphrena globosa, C. quinoa, C. amaranticolor, C. murale) resulted in infection of one C. amaranticolor plant. This positive plant was used as source for successful mechanical inoculation to C. quinoa, C. murale, and C. amaranticolor as confirmed by positive PCR results in all test plants. These plants showed systemic symptoms like mosaic and rugosity, but were negative for PVS by DAS-ELISA. Attempts to transmit the PVS from arracacha CIP204060 using Myzus persicae and Macrosiphum euphorbiae to indicator plants or potato were not successful. Using additional primers, we determined the sequence of the 3′ 3,094 nts of the virus genome, including the partial RdRp, triple gene block and CP genes, from accession CIP204060 (GenBank accession no. KY451037). The partial replicase sequence (88% aa identity) identified this virus as PVS, but the identity in aa of CP (79%) is close to the species demarcation limit (80%) of carlaviruses. Nevertheless, symptoms in Chenopodium plants were like PVSA. Phylogenetic trees built based on CIP204060 using CP, 7 kDa protein, and 11 kDa protein, located this PVS isolate to a new branch distinct and basal to the ordinary and Andean strain clusters. Other carlaviruses have been reported in arracacha (Hermann 1997; Phillips 1990), but they had clear differences in host range; moreover, nucleotide sequences are lacking to compare them. Unlike its other reported natural hosts, arracacha is not from the Solanaceae and indicates PVS could pose a threat to a broader range of crops than previously known.